Seroepidemiological Survey of Human Hydatidosis in Patients Referred to the Health Service Centers of Hamadan in 2019 - Mohammad Fallah; Seyedmousa Motavallihaghi; Mehran Bakhtiari (Shahrekord University of Medical Sciences, 2022)
Background and aims: According to evidence, a hydatid cyst is one of the most important health issues in most parts of the world. This study aimed to investigate the frequency of human hydatidosis in patients referred to health service centers in Hamadan province in 2019 using the enzyme-linked immunosorbent assay (ELISA) method. Methods: In this cross-sectional study, blood samples were collected from 300 patients referred to medical diagnostic laboratories in Hamadan and evaluated for the presence of immunoglobulin G antibodies against hydatid cysts by ELISA. The data were analyzed using SPSS software. Results: Out of 300 samples, 16 (5.3%) cases were positive, including 10 (5.6%) cases of the residents of urban areas and 6 (4.9 %) cases from those residing in rural areas. Moreover, of all the positive cases, 8 (50%) cases were males and 8 (50%) cases were females. The highest percentage of infection (45.5%) was observed in the age group 20-30 years. Conclusion: The findings indicated that human hydatidosis is a public health problem in this province. The implementation of control and prevention programs, as well as increasing the knowledge of people, can help in controlling and reducing infection in humans and livestock.